Pengembangan Materi Ajar Teks Anekdot berbasis Android menggunakan Model Abee (Anekdot Bee) - Wiwit Rizqiani (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The research on the development of teaching materials for anecdotal texts based on Android using the Abee model (Anecdotal Bee) is motivated by the difficulty in implementing learning media in one class with another. Efforts to overcome these problems are by developing teaching materials for anecdotal texts based on Android using the Abee model. The purpose of the study is to provide new insights into the use of media as a development of teaching materials based on Android. The method used is a descriptive model of the quantitative method which is then described to make it easier for readers. Based on the results of the prototype test design for the development of teaching materials for anecdotal texts based on Android using the Abee model, it can be declared feasible through the results of expert judgment assessments, namely material experts, media experts, and Indonesian language teachers for class X. In the Aiken's V formula, it is stated that it is valid if the index range reaches a range of 0.00 - 1.00 so that the results of the indicator item test show a result of 0.875, it is considered high enough to support the overall indicator device. The results of this study can be applied to Basic Competencies 3.6 analyzing the structure and language of anecdotal texts and 4.6 recreating anecdotal texts by paying attention to the language structure. In this study, it can be concluded that the development of android-based anecdotal text teaching materials using the abee model using the ADDIE research model, namely analysis, design, development, implementation, and evaluation. According to the results of the research questionnaire, the abee application is good in terms of content, but the content needs to be expanded.